Landau, a great physicist and teacher - Livanova, Anna (Pergamon Press, 1980)
A biography of Lev Landau, one of the greatest Soviet theoretical physicists, whose career was cut short by a catastrophic car accident in 1962 and who was still only sixty when he died six years later. He won the Nobel Prize 'for pioneering work on the theory of the condensed state of matter, particularly liquid helium'. But the book shows that Landau's characterisation of himself as 'one of the last of the universal men of theoretical physics' was fully justified. Clearly and concisely it describes his achievements in all areas of theoretical physics from hydrodynamics to the quantum theor.